Youth participation in horticultural and poverty reduction in rural areas: A case study of horticultural production in Mvomero district, Tanzania - Gulamiwa, George Nyalulu (Mzumbe Univesity, 2023)
A Research Report Submitted to the Institute of Development Studies in Partial Fulfillment of the Requirements for the Award of Master Degree in Development Policy (MSc DP) of Mzumbe University